The Creation of Regional Dependency - Matthews, Ralph, 1943- (Book collections on Project MUSE., 1983)
Matthews, in a lucid, systematic analysis of regionalism and regional underdevelopment in Canada, takes us through the academic cant, political puffery, and bureaucratic bumbling to show how regional disparity and regional underdevelopment are the result of exploitation by powerful central Canadian interests.